Seismic performance of gravity quay wall. Issue 1 (February 2021) - Aldelfee, Alaa N.; Aldefae, Asad H.
Abstract: Understanding the mechanism of the damages that occurs and the amount of displacement due to sliding in the gravity quay wall in ports during earthquakes are important factors because of the increase in the incidence of seismic disasters during recent decades. For this purpose, the investigation was performed using a shaking table test for two models of the quay wall in dry and saturated conditions. Cohesionless soil is used as a foundation for the quay wall and rubble soil used as a filter behind the quay wall and underneath. The dynamic performance of the quay wall is assessed in terms of both of the acceleration response and the seismic displacement. The results showed that the seismic wave amplification is increased significantly from the foundation of the gravity quay wall to the surface of the model, in which the highest amplification happened at the top of the quay wall model, thus, the design of this part of the gravity quay wall type caisson needs a great amount of the care and accurateness because the possibility of generating and propagating the cracks in this zone are very high.